TINGKAT KESIAPAN PETANI KELAPA SAWIT MANDIRI DALAM MENGHADAPI PEREMAJAAN KEBUN (REPLANTING) DI NAGARI TARATAK INGGI KECAMATAN TIMPEH - anang safadri anangsfd17; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2023)
ABSTRACT This study aims to determine: 1) Knowledge of oil palm farmers in Nagari Taratak Tinggi about oil palm cultivation, 2) Condition of oil palm farmers in Nagari Taratak Tinggi and replanting techniques, 3) Readiness of the cost of oil palm farmers in Nagari Taratak Tinggi for replanting. . The type of research conducted is descriptive quantitative research, the number of samples in this study as many as 588 families who own oil palm with the category > 20 years, the sampling technique used snowball sampling, the data collection technique was by giving questionnaires to the respondents and the analysis technique used the Guttman scale. The results of the analysis found that the level of knowledge of farmers about oil palm cultivation in Nagari Taratak Tinggi is mostly less with a percentage of 46.8%, enough with a percentage of 33.9%, while the good category is only 19.4%. Most of the farmers' oil palm plantations have met the criteria for replanting. As many as 51.8% of farmers have sufficient knowledge about the techniques of rejuvenating oil palm plantations. In financing for replanting, there are no farmers who are ready to do rejuvenation, most of the farmers do not have adequate financial preparations and even many do not have any inventory at all. The overall level of readiness of oil palm farmers is none of the farmers who are really ready to face replanting, where the cost factor is the main obstacle for farmers to carry out replanting due to lack of preparation costs.